Textural properties of VO/TiO catalysts obtained from VOCl - C. Martin; V. Rives (Adsorption Science & Technology, 1985)
V 2 O 5 /TiO 2 systems have been obtained by reacting TiO 2 (P-25 from Degussa, ca 55% anatase, or a rutilised modification, ca 3% anatase) with gaseous VOCl 3 . The samples have been characterised by X-ray diffraction, UV–Vis spectrophotometry and nitrogen adsorption at 77 K. For the anatase carrier, a monolayer coverage of V 2 O 5 is achieved, but only 0·46 monolayers are formed with the rutilised support. The specific surface areas decrease upon incorporation of V 2 O 5 , and that seems to be well dispersed without forming crystallites.